Rurality and readiness: Addressing substance use via a community-level assessment - Cureton, Jenny L. (Journal of addictions & offender counseling, 2022)
Counselors serve diverse clients who may experience substance use issues and contributing factors such as generational poverty and isolation. A rural region of a state with legalized marijuana engaged in an assessment of community readiness to address the use of alcohol, tobacco, marijuana, and other substances. Scoring and thematic analysis of interviews with 30 community members resulted in scores for five readiness dimensions and themes concerning contributors to and detractors from readiness. Recommendations for counselors span prevention, intervention, and advocacy to support individuals, families, and organizations seeking to promote awareness and addiction recovery, particularly in the context of rural poverty.